PENGARUH PERSEPSI GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA PADA KARYAWAN BLITZMEGAPLEX TERAS KOTA - Astried Fitri Karnita (Journal of Research and Measurement in Psychology, 2012)
Abstract The research was aimed to determine influence of perception of leadership styles toward job satisfaction among the employee in Blitzmegaplex Teras Kota. Dimensions of leadership styles in this research are participative, caregiver, authoritarian, bureaucratic, and task-oriented leadership styles. Dimensions of job satisfaction are hygiene factors and motivators. Methods of data collection in this research used leadership styles and job satisfaction scales. Sampling technique was purposive sampling to obtained a sample of 30 people. Analysis of the data used is regression analysis. The result of this research explain that there is a significant influence of perception of leadership styles toward job satisfaction among the employee in Blitzmegaplex Teras Kota, with a correlation coefficient (rxy) is 0,523 and R Square (R2) is 0,273. The magnitude show that the variable of job satisfaction accounted for by variable leadership styles as much as 27%. This means that as much as 27% of the leadership style variables influence to job satisfaction, and vice versa. This can be used as guidelines for companies to improve the style of leadership in order to increase employee job satisfaction, and maintain company productivity. From this result, it is suggested that other variables which have not been revealed such as the fulfillment of expectations of salary, interpersonal relations, work environment and physical condition, can be further studies. Keywords: Perception of Leadership Style, Job Satisfaction